Empowering women to protect wildlife in former hunting tourism zones: a political ecology of Akashinga, Zimbabwe. Issue 5 (4th May 2023) - Mkono, Mucha; Rastegar, Raymond; Ruhanen, Lisa
Abstract: Anti-poaching is an important component of the tourism management system for destinations that rely on wildlife as their key attraction. The present paper, broadly grounded in political ecology, explores how social justice tenets are used to frame and implement anti-poaching initiatives in Sub-Saharan Africa. In particular, the study examines the Akashinga model, a Zimbabwean woman-only anti-poaching initiative founded by the Australian conservation activist, Damien Mander. Political ecology lends itself well to the analysis of social justice initiatives as it unpacks how political, economic and social factors interact with environmental issues and changes. Akashinga is particularly compelling as a socially innovative conservation model intended to replace hunting tourism in Sub-Saharan wilderness areas. Data were collected from a rich selection of online sources, including social media and relevant websites. Our analysis reveals Akashinga's framing and modus operandi as premised three dimensions: community involvement, the empowerment of women, and the superiority of women in achieving anti-poaching success and broader conservation outcomes. It is argued that, while Akashinga makes a positive contribution to the local community and wildlife conservation efforts, there are important caveats to consider, in the context of postcolonial power relations.